Anomalous field effect and slow relaxation in an AlGaN/GaN quantum well. (23rd April 2020) - Tu, Huayao; Gao, Kuanghong; Zhang, Songran; Yu, Guolin; Sun, Yan; Kang, Tingting; Chen, Xin; Dai, Ning
Abstract: Here we report the observation of the anomalous field effect, manifested as apparent electric hysteresis and decreasing resistance in the negative gate bias region in an Al0.087 Ga0.913 N/GaN heterostructure quantum well at low temperature. Together with this, slow relaxation of resistivity was observed. Magnetotransport measurements were carried out to determine the origin of such phenomena. The results show that the origin of electric hysteresis and slow relaxation is the capture and release of electrons by traps located in regions of the device structure outside of the conducting 2DEG channel. Besides, the existence of slow dynamics at only low temperature indicates that the traps involved should be shallow impurities. As for the anomalous reduced resistance when applying negative gate bias, it should come from the increase of mobility, which is due to the dominant role of interface roughness scattering at low temperature.